2021
DOI: 10.3390/ani11010188
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnographic Account of the British Equestrian Virtue of Bravery, and Its Implications for Equine Welfare

Abstract: This article describes the virtue of bravery in British equestrian culture and suggests that riders’ tactics for bolstering bravery may have negative implications on equine welfare. These observations are based on 14 months of ethnographic research among amateur riders and the professionals who support them (n = 35), utilising participant observation and Dictaphone recordings. Riders suffering from ‘confidence issues’ could be belittled and excluded. Instructors’ approaches towards bolstering bravery involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…The issue of human welfare and safety being sometimes de-prioritised compared to equine wellbeing aligns with previous studies, which have shown that danger, hardship and endurance are expected parts of equestrianism [ 19 , 30 ]. As “serious leisure” enthusiasts [ 4 ], the equestrian community show commitment to their horses in the face of adversity.…”
Section: Discussionsupporting
confidence: 80%
“…The issue of human welfare and safety being sometimes de-prioritised compared to equine wellbeing aligns with previous studies, which have shown that danger, hardship and endurance are expected parts of equestrianism [ 19 , 30 ]. As “serious leisure” enthusiasts [ 4 ], the equestrian community show commitment to their horses in the face of adversity.…”
Section: Discussionsupporting
confidence: 80%
“…However, it is more likely that the higher median age of this sub-sample means that they have potentially been around equines for longer and may therefore be expected to have accumulated more equine-related injuries than younger respondents (who are typically at lower risk of contracting COVID-19). The culture of UK equestrianism where taking risks is normalised may also contribute to this finding [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two farms differed in ownership (state-owned vs. privately-owned), herd size (1500 vs. 11,000), farm age, location, and many other factors; the findings from these farms are not generalizable to all Chinese farms, but key aspects may be transferable to farms with similar contexts. Ethnography has rarely been applied in the field of animal welfare [ 32 ], and our results illustrate how the application of this methodology can provide researchers with nuanced insights into the experiences of farm workers…”
Section: Discussionmentioning
confidence: 75%
“…As ethnographies have rarely been used in animal welfare research [ 32 ], we first describe ethnography and clarify what our study intends to achieve. Ethnographies are methods used to understand social groups and involve immersive fieldwork and participant observation [ 31 ].…”
Section: Methodsmentioning
confidence: 99%